Realist and Historicist Modes of Critique in Critical Sociology. (July 2023) - Desan, Mathieu Hikaru
There are two distinct modes of critique operative in Bourdieu's 'critical sociology'. Bourdieu sometimes engages in what I call the realist mode of critique. This is premised on the idea that naïve experience of the social world dissimulates real relations of domination, which critique then reveals. At other times, Bourdieu engages in what I call the historicist mode of critique, which denaturalizes the doxic experience of the social order by demonstrating its arbitrary character. Whereas realist critique claims that the social world really is other than it appears, historicist critique suggests that it could be otherwise. This tension between the two modes of critique is not unique to Bourdieu, but also present in the Polanyian literature and in the Western Marxist tradition. By distinguishing between the two modes of critique, my aim is to clarify an oft-implicit division that cuts across different critical traditions in the social sciences.